Screening of peat soil bacterial isolates producing antibacterial compounds against Salmonella Typhi and Extended-Spectrum Beta-Lactamase (ESBL)-producing Escherichia coli - Munawarah Fuaddah; Dede Mahdiyah; Risyda Komaliya; Putri Vidiasari Darsono (Ananda - Health & Education Foundation, 2026)
Background: Peat soil, with its acidic pH and high organic content, supports diverse microorganisms capable of producing secondary metabolites with potential antibacterial activity. These compounds may serve as new sources for antimicrobial development. Objective: This study aimed to evaluate the antibacterial potential of bacterial isolates from peat soil against Salmonella typhi and Extended-Spectrum Beta-Lactamase (ESBL)-producing Escherichia coli. Method: Bacterial isolation was performed using the pour plate method on Trypticase Soy Agar (TSA) medium. Antibacterial activity was assessed using the well diffusion method, while the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined through broth dilution and spread plate techniques. Data were analyzed using descriptive statistics. Results: Fourteen bacterial isolates were obtained, all of which were Gram-negative bacilli. Isolate 5.1 exhibited the highest inhibitory activity, with inhibition zone diameters of 16.06 mm against ESBL-producing E. coli (intermediate category) and 7.53 mm against S. Typhi (resistant category). The MIC value for active isolates was 5 mg/mL; however, no bactericidal effect was observed within the tested concentration range (5–10 mg/mL). Conclusion: Peat soil bacteria demonstrated antibacterial potential, with three isolates showing activity against ESBL-producing E. coli and one isolate active against S. Typhi at 5 mg/mL. Further studies are required to identify the active compounds and elucidate their mechanisms of action.